2014
DOI: 10.1073/pnas.1409203111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA 3′ pp 5′ G capping on repair reactions at DNA 3′ ends

Abstract: Many biological scenarios generate "dirty" DNA 3′-PO 4 ends that cannot be sealed by classic DNA ligases or extended by DNA polymerases. The noncanonical ligase RtcB can "cap" these ends via a unique chemical mechanism entailing transfer of GMP from a covalent RtcB-GMP intermediate to a DNA 3′-PO 4 to form DNA 3′ pp 5′ G. Here, we show that capping protects DNA 3′ ends from resection by Escherichia coli exonucleases I and III and from end-healing by T4 polynucleotide 3′ phosphatase. By contrast, the cap is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Intriguingly, reversibility of the serine hydrogen bond donor/acceptor would also enable the recognition of guanine in the lesion-binding pocket. Consistent with this, SpAptx has recently been reported to catalyze removal of GMP from 3’–GMP–capped DNA ends (Das et al, 2014). We speculate that GMP binds in an analogous manner to AMP during a deguanylation reaction.…”
Section: Detection Of 5’-adenylated (5’–amp) Lesionsmentioning
confidence: 55%
“…Intriguingly, reversibility of the serine hydrogen bond donor/acceptor would also enable the recognition of guanine in the lesion-binding pocket. Consistent with this, SpAptx has recently been reported to catalyze removal of GMP from 3’–GMP–capped DNA ends (Das et al, 2014). We speculate that GMP binds in an analogous manner to AMP during a deguanylation reaction.…”
Section: Detection Of 5’-adenylated (5’–amp) Lesionsmentioning
confidence: 55%
“…Initially described as an adenylate decapping enzyme acting on abortive AppDNA intermediates formed by ATP-dependent DNA ligases, aprataxin was subsequently shown to have 3= decapping activity on a DNAppG end formed by E. coli RtcB (12,24) and on DNAppA ends generated by an ATP-dependent thermophilic RNA ligase (38). Here, we extend the aprataxin repertoire by showing that it can remove a 5= guanylate cap from GppDNA formed by M. xanthus RtcB3.…”
Section: Discussionmentioning
confidence: 77%
“…The DNA repair enzyme aprataxin has a DNA 3= decapping activity whereby it converts DNAppG (synthesized by E. coli RtcB) to DNAp and GMP (12,24). Aprataxin is a member of the histidine triad family of nucleotidyltransferases that act via a covalent enzyme-(histidinyl)-NMP intermediate.…”
Section: =mentioning
confidence: 99%
See 1 more Smart Citation
“…It is first activated by the transfer of GMP from the RtcB-GMP complex to form the 3Ј-guanylated intermediate RNA 3Ј pp 5Ј G. This intermediate is then ligated to the 5Ј-hydroxyl of an RNA acceptor to form a phosphodiester bond or to the adjacent 2Ј-OH to form a cyclic phosphate. Moreover, recent studies showed potential for this activity to be involved in DNA repair (15,16).…”
mentioning
confidence: 99%